ASSOCIAÇÃO ENTRE O USO PROLONGADO DE TELAS E O CONSUMO ALIMENTAR DE INDIVÍDUOS ADULTOS: UM ESTUDO NACIONAL (REMUNOM, 2025)
The increase in the time of exposure to electronic devices has raised concerns about the health consequences, especially with regard to eating habits. Thus, the present study aimed to evaluate the association between prolonged screen use and food consumption in Brazilian adults. This is a cross-sectional, population-based study, carried out with data from the VIGITEL (Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico) system from 2023. Individuals aged 18 to 30 years, residing in Brazilian capitals, were included. Screen time was considered prolonged when more than three hours per day. Food consumption was analyzed based on markers of natural and ultra-processed foods (UPF), considering regular consumption and on the day before the interview. A total of 3,732 participants were included, the majority of whom were female (51.73%), and 19.08% were obese. The prevalence of prolonged screen use was 78.12%. A significant association was identified between prolonged screen time and the consumption of five or more UPFs (PR: 1.42; 95% CI: 1.08–1.86; p = 0.01), in addition to an association with the consumption of chocolate drinks, processed meats, industrialized condiments and margarine, regardless of age, sex and body mass index. The findings indicate that adults who spend more time in front of screens are more likely to have inadequate dietary patterns, with a predominance of UPFs. It is concluded that excessive screen use may be a relevant risk factor for unhealthy food consumption.